Not on your list, but an easy way is
.. a) swap coefficients of x and y, negating one. (Now you have 2x -3y.)
.. b) set any constant term to zero (now you have 2x -3y = 0)
.. c) translate the line to the point (5, 2) by substituting x ⇒ x-5, y⇒ y-2
2(x -5) -3(y -2) = 0
The way you've been taught, selection C is the proper choice.
I don't know what to say, I've been trying to explain this for like... 10 minutes but I can't think of how to explain it. All I can say is to just divide .8 by 10. The answer is .08.
Answer:
Option D. (x + 4)(x + 1)
Step-by-step explanation:
From the question given above, the following data were obtained:
C = (6x + 2) L
D = (3x² + 6x + 9) L
Also, we were told that half of container C is full and one third of container D is full. Thus the volume of liquid in each container can be obtained as follow:
Volume in C = ½C
Volume in C = ½(6x + 2)
Volume in C = (3x + 1) L
Volume in D = ⅓D
Volume in D = ⅓(3x² + 6x + 9)
Volume in D = (x² + 2x + 3) L
Finally, we shall determine the total volume of liquid in the two containers. This can be obtained as follow:
Volume in C = (3x + 1) L
Volume in D = (x² + 2x + 3) L
Total volume =?
Total volume = Volume in C + Volume in D
Total volume = (3x + 1) + (x² + 2x + 3)
= 3x + 1 + x² + 2x + 3
= x² + 5x + 4
Factorise
x² + 5x + 4
x² + x + 4x + 4
x(x + 1) + 4(x + 1)
(x + 4)(x + 1)
Thus, the total volume of liquid in the two containers is (x + 4)(x + 1) L.
Answer:
45 is answer I guess cuz my teacher taught me just like that
Answer- 3x-56(x) =8
Explanation- Good luck